Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1038/sj.gt.3301160
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular administration of E7-transfected dendritic cells generates the most potent E7-specific anti-tumor immunity

Abstract: Dendritic cells (DCs) are highly efficient antigen-presenting cells capable of priming both cytotoxic and helper T cells in vivo. Recent studies have demonstrated the potential use of DCs that are modified to carry tumor-specific antigens in cancer vaccines. However, the optimal administration route of DC-based vaccines to generate the greatest anti-tumor effect remains to be determined. This study is aimed at comparing the levels of immune responses and anti-tumor effect generated through different administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 26 publications
2
94
0
Order By: Relevance
“…an important one. It is well established that DC can stimulate primary immune responses (7,10,19,25,26,63,64), and our data confirm this point. However, our data show that M⌽ can also stimulate T cells in vivo to proliferate, express effector functions, and mature into memory cells.…”
Section: Figure 10 M⌽ and Dcs Directly Stimulate Naive P-14 Cd8supporting
confidence: 80%
“…an important one. It is well established that DC can stimulate primary immune responses (7,10,19,25,26,63,64), and our data confirm this point. However, our data show that M⌽ can also stimulate T cells in vivo to proliferate, express effector functions, and mature into memory cells.…”
Section: Figure 10 M⌽ and Dcs Directly Stimulate Naive P-14 Cd8supporting
confidence: 80%
“…Generation of luciferase-expressing E7-specific CD8 + T cells. An E7-specific CD8 + T cell line has been previously described (24). To generate a luciferase-expressing E7-specific CD8 + T cell line, we first created a retrovirus containing luciferase (pLuci-thy1.1 construct), which expressed both luciferase and thy1.1.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated the potential use of DCs that are modified to carry tumor Ags in cancer vaccines (20). DC-based vaccines including DCs loaded with E7 peptide or proteins, DCs fused with tumor cells, and DCs transduced with the E7 gene or viral vectors have been used in cervical cancer models (21)(22)(23)(24).…”
Section: H Uman Papillomavirus (Hpv)mentioning
confidence: 99%